Optimizing delivery strategies for 3HP TB preventive treatment in Tanzania: A qualitative study on acceptability of family approach in HIV care and treatment centers. - Doreen Pamba; Erica Sanga; Killian Mlalama; Lucas Maganga; Chacha Mangu; Anange Lwilla; Willyhelmina Olomi; Lilian Tina Minja; Issa Sabi; Riziki Kisonga; Emmanuel Matechi; Isaya Jelly; et al. (PLOS Global Public Health)
Tanzania rolled-out a 12-dose, weekly regimen of isoniazid plus rifapentine (3HP) TB preventive treatment in January 2024. The 3HP completion rate is generally ≥80%, varying by delivery strategy and programmatic setting. Before the roll-out, a mixed methods study was conducted to assess whether a family approach involving family member support, SMS reminders, and three health education sessions was acceptable and optimized 3HP uptake and completion. This paper describes acceptability of the family approach among people living with HIV (PLHIV), treatment supporters (TS), and community health workers (CHWs). This was a qualitative descriptive study in 12 HIV care and treatment centers across six administrative regions. We purposively sampled 20 PLHIV, 12 CHWs for in-depth interviews, and 23 TS for three focus group discussions held between September and December 2023. The theoretical framework of acceptability guided thematic-content analysis using a framework approach. Participants understood that PLHIV have an increased risk for active TB and that 3HP provides shortened treatment for TB disease prevention. They learned about TB and 3HP through health education sessions, but participation of TS was low due to expensive transportation costs to clinics. Receiving support from a trusted person and SMS were perceived as good adherence reminders. The majority reported mild self-limiting side effects but expressed positive attitudes because of the shortened treatment, TB counseling, satisfaction from helping others, lifestyle and work alignment, and reduced work burden. Some PLHIV had difficulties identifying supportive family members, so they chose close friends or CHWs. The family approach to supporting 3HP adherence is widely accepted by PLHIVs, TS, and CHWs in the context of person-centered care that respects their preferences. We recommend its adoption in programmatic settings as a combined approach, considering changes made during the study. However, further research is warranted to assess its acceptance among other populations eligible for 3HP.